Prevalence of intestinal parasites and Helicobacter pylori co-infection in people with gastrointestinal symptoms in Africa: a systematic review and meta-analysis - Yenesew Mihret Wondmagegn; Getu Girmay; Gashaw Azanaw Amare; Muluneh Assefa; Mebratu Tamir; Zufan Yiheyis Abriham; Abebaw Setegn (BMC Infectious Diseases)
Abstract Background Gastrointestinal infections caused by intestinal parasites and Helicobacter pylori are significant public health issues in Africa, where poor sanitation and limited access to healthcare contribute to high disease burden. Since there was no previous pooled data regarding the intestinal parasites and Helicobacter pylori co-infections among gastrointestinal symptomatic patients in the African context, this review aimed to determine the overall prevalence of intestinal parasites and Helicobacter pylori co-infection in people with gastrointestinal symptoms in Africa. Methods The current review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) standards and registered in the International Prospective Register of Systematic Reviews (PROSPERO; CRD42024598993). A comprehensive search was conducted across electronic databases: PubMed, Medline, EMBASE, Google Scholar, Web of Science, Science Direct, and African Journals Online. The data was extracted using Microsoft Excel 2010 and analyzed using STATA version 11.0 Software. A random-effects model was used to calculate the pooled effect size of outcome variables across studies, with a 95% confidence interval. The I2 statistic was employed to assess heterogeneity. A funnel plot and Egger’s test were used to identify publication bias. A p-value < 0.05 indicated statistically significant publication bias. Results The combined prevalence of intestinal parasites and H. pylori co-infections was 31.03% (95% CI: 18.66–43.39) with significant heterogeneity (I2 = 98.9%, p = 0.000). The Subgroup analysis revealed that Egypt and Ethiopia had the highest and lowest rates of intestinal parasites and H. pylori co-infection respectively at 39.84% (95% CI: 27.79–51.88%), and 5.86% (95% CI: 4.10–7.62). Moreover, the adjusted Egger’s regression test did not reveal any publication bias (p = 0.116). Conclusion This meta-analysis shows a significant prevalence of intestinal parasites and H. pylori co-infection in Africans with gastrointestinal symptoms. The coexistence of these diseases creates diagnostic and therapeutic problems. Thus, the findings underscore need for targeted interventions and further research is needed to develop effective control strategies to reduce the impact of these illnesses on public health in Africa.